2002
DOI: 10.1074/jbc.m207990200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Two Nuclear Complexes to a Novel Regulatory Element within the Human S100A9 Promoter Drives the S100A9 Gene Expression

Abstract: S100A9, also referred to as MRP14, is a calcium-binding protein whose expression is tightly regulated during differentiation of myeloid cells. The present study was performed to study the cell type-and differentiationspecific transcriptional regulation of the S100A9 gene. Analysis of the S100A9 promoter in MonoMac-6 cells revealed evidence for a novel regulatory region from position ؊400 to ؊374 bp, termed myeloid-related protein regulatory element (MRE). MRE deletion resulted in a 5.2-fold reduction of promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 48 publications
(38 reference statements)
2
34
0
Order By: Relevance
“…[13,14]). The expression of the two S100 proteins is restricted to a specific stage of myeloid differentiation, probably driven by a recently characterized regulatory element [15]. In addition to the binding to Ca 2ϩ , S100A8/A9 has been shown to bind other bivalent cations, such as Zn 2ϩ and Cu 2ϩ [4, 16 -19].…”
Section: Introductionmentioning
confidence: 99%
“…[13,14]). The expression of the two S100 proteins is restricted to a specific stage of myeloid differentiation, probably driven by a recently characterized regulatory element [15]. In addition to the binding to Ca 2ϩ , S100A8/A9 has been shown to bind other bivalent cations, such as Zn 2ϩ and Cu 2ϩ [4, 16 -19].…”
Section: Introductionmentioning
confidence: 99%
“…The S-100A8/A9 complex was reported to specifically bind to polyunsaturated fatty acids in a calcium-dependent manner [31,32], and it has been implicated in the modulation of the activity of arachidonic acid-metabolizing enzymes [33]. Neuronal activity during SD that is mediated by the NMDA receptor could help propagate astrocytic calcium waves into the brain areas contralateral to the affected side [34 -36].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of S100A8 and S100A9 genes could be regulated in either harmonized or independent ways. Some studies have suggested a more important role of S100A9 than S100A8 (17,18), and cis-elements for trans-activation on the human S100A9 gene have been well documented (19,20). Thus, we focused on the mechanisms underlying S100A9 trans-activation in HaCaT cells exposed to As(III).…”
Section: Resultsmentioning
confidence: 99%
“…A study with human mature monocytic Mono Mac 6 cells, which exhibit high S100A9 expression under steady-state conditions (20), showed that expression of S100A9 was dependent on the two regions in the promoter of the S100A9 gene, from 153 to 361 (first intron) and from -400 to -374 (promoter region). Additionally, the Kruppel-related zinc finger protein and the transcriptional intermediary factor 1β (TIF1β) were shown to bind to the region from -400 to -374 in the promoter of the S100A9 gene, resulting in the upregulation of S100A9 expression (19,20). Further studies are required to clarify whether the Kruppel-related zinc finger protein and TIF1β are activated by As(III) in HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%